Assessment of the side thrust for off-road tracked vehicles based on the punching shear theory. (October 2018) - Baek, Sung-Ha; Shin, Gyu-Beom; Chung, Choong-Ki
Highlights: A proper assessment of the bottom and side thrusts of the track system is essential. Previous prediction models for the soil thrust tend to underestimate the side thrust. Punching shear failure takes place along the side of the track system. A prediction model for the side thrust is developed based on the punching shear theory. Abstract: The track system is generally applied for heavy off-road vehicles. While moving on the off-road, the track system horizontally transmits an engine torque to the soil-track interface, resulting in slip displacement and an associated soil thrust acting as a traction force. As soil thrust is developed on the bottom and the side of the track system (hereinafter referred to as "bottom thrust" and "side thrust", respectively), it is imperative to evaluate both the bottom thrust and the side thrust to assess the off-road tracked vehicle's performance. Unlike the bottom thrust, however, the mechanisms of the side thrust have not been fully understood. To address this, this study aimed to evaluate the side thrust for off-road tracked vehicles. A new mechanism for the side thrust was theoretically investigated based on the punching shear theory. A series of model track experiments were conducted on a model track system with silty sand. From the experiment results, the shapes of the failure surface were observed, and the side thrust was measured for verification purposes. Particular attention was given to the development of a side thrust prediction model for the heavy off-road tracked vehicles based on the proposed mechanism.